Komposit Berbasis Serat Tangkos Kelapa Sawit: Kajian Fisik dan Mekanis - Zaqy, Sandi Yudha Barri; Utama, Satrio Darma; Pramanda, Wibi (Universitas Muhammadiyah Metro, 2025)
This research explores the use of oil palm empty fruit bunch waste fibers as an environmentally friendly reinforcement material for composite applications, aiming to replace conventional materials. The fabrication process utilized empty fruit bunch fibers, resin, and polylactic acid (PLA), with components produced using 3D printing technology. Mechanical properties were evaluated through tensile testing (ASTM D3039), compressive testing (ASTM D695), and Vickers microhardness testing (ASTM E384). The results showed an average maximum tensile strength of 8.18 MPa, while compressive testing yielded a maximum strength of 3.95 MPa. Vickers hardness values ranged from 19.53 to 29.04, with an average of 25.73. These findings highlight the potential of empty fruit bunch fiber composites as an alternative material that supports waste reduction and sustainability in the palm oil industry. However, further optimization of fiber fraction and surface treatment is needed to improve mechanical performance. This study not only contributes to scientific knowledge but also opens opportunities for sustainable material innovation in engineering applications